Comparative study of the antioxidant effect of three Aloe species - Derouiche Mourad; Chkird Fadoua; Ziani Anas; Boukhaffa Chaymae; Lafdil Mohamed; Alla Anass; Arabi Mourad; Abdelbasset Berrichi; Noureddine Kouddane (E3S Web of Conferences)
Research into antioxidants in plants has expanded greatly in recent years, to find the best posible antioxidants to prevent and even treat disease. This study represents the first comparative investigation of the antioxidant activity of these three Aloe species (Aloe vera, arborescens and brevifolia). The 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay was used to assess the antioxidant activity of methanolic extracts of the three Aloe species. A calibration range of a standard antioxidant represents the positive control, Butylhydroxyanisol (BHA) (0-100 µg/ml). The results showed a significant difference in the free radical scavenging activity of the three Aloe species and the standard (BHA) for DPPH, with respective IC50 values from lowest to highest of 0.040 mg/ml for standard BHA, 0.100 mg/ml for Aloe vera, 0.270 mg/ml for Aloe arborescens and 0.370 mg/ml for Aloe brevifolia. The percentage of inhibition in Aloe vera is higher than in the other two species (Aloe arborescens and brevifolia). Aloe vera, which is very rich in active substances, showed high antioxidant potential comparable to that of the standard. Leaf extracts from Aloe arborescens and Aloe brevifolia also had a lower antioxidant potential than Aloe vera, but this was not negligible.